Evaluación de tres abonos orgánicos en el cultivo de fréjol variedad cuarentón (Phaseolus vulgaris L.). - Gallo Cevallos, Jower Armando (2024)
The present research was developed on the farm owned by Mr. Robinson Aranda, located in La Maná canton, to evaluate three organic fertilizers in the cultivation of common bean (Phaseolus vulgaris L.), a trial was established with a Design of Complete Random Blocks, the fertilizers tested were Max Black Pearl 2 Kg/m², Bioabor in a dose of 2.5 Kg/m², and the slaughterhouse waste fertilizer with a dose of 2.5 Kg/m² and control, with four treatments, five repetitions, and 10 experimental units. The variables evaluated were: germination percentage, plant height (cm), number of pods, pod weight (g), total production (g), and cost analysis per treatment. The results obtained were the following a high percentage of germination was reported, 80% of 600 seeds that underwent the germination process, and the highest plant height was achieved with the Max Black Pearl organic fertilizer with an average of 26.90 cm. ; Regarding the number of pods, it was possible to obtain a higher average with treatment T1 with 17 pods, two harvests were carried out, the highest weight per treatment was for T1 with 208.20 g, after the second harvest, treatment T1 was the one that reported the highest production with 3089 grams, in terms of cost analysis, treatment T1 recorded a higher average income than the other treatments in the study, $6.18. With the application of 2 Kg/m² of fertilizer 1, the forty bean crop had a better response in the morphoagronomic indicators.